Bimetallic Ni0.4Mn1.6P derived from nickel functionalized a new Mn metal-organic framework for supercapacitor. (March 2021) - Wang, Yi; Chen, Lijun; Lin, Shaomin; Wu, Guangwei; Luo, Jun; Yang, Huan; Qin, Hui
Graphical abstract: Highlights: A new 2D Mn-MOF (Mn-PRCA, PRCA = pyrazine 2, 3-dicarboxylic anhydride) is constructed and used as a host for the loading of Ni 2+ through post-synthetic modification method (PSM). The obtained Ni0.4 Mn1.6 P is used as electrode material and exhibit large specific capacity of 1060 F/g at 1 A g and a 75 % capacitance retention after 2000 cycles. This is the first time that PSM technique is applied in electrochemical application and bimetal phosphide derived from a new MOF is used as electrode materials for supercapacitor. Abstract: A new 2D Mn-MOF (Mn-PRCA, PRCA = pyrazine 2, 3-dicarboxylic anhydride) is constructed and used as a host for the loading of Ni 2+ through post-synthetic modification method (PSM). Then the bimetal MOF(Ni@Mn-PRCA) is served as template for the synthesis of Ni0.4 Mn1.6 P by the phosphorization route. The obtained Ni0.4 Mn1.6 P is used as electrode material and exhibit a large specific capacitance of 1060 F/g at 1 A g and a capacitance retention of 75 % after 2000 cycles). In addition, an asymmetric device Ni0.4 Mn1.6 P // AC (activated carbon) is also assembled and shows an energy density of 21.1 W h kg −1 at the power density of 799.6 kW kg -1 under a stable working voltage of 1.6 V. This is the first time that PSM technique is applied in electrochemical application and bimetal phosphide derived from a new MOF is used as electrode materials for supercapacitor.